Pengaruh Komisaris Independen, Kepemilikan Institusional, dan Koneksi Politik terhadap Tax Avoidance pada Perusahaan Sektor Basic Materials yang Terdaftar di Bursa Efek - Dewi Nurul Khusna; Risky Budianto (AKUNTANSI 45, 2026)
The objective of this study is to examine the effect of independent commissioners, institutional ownership, and political connections on tax avoidance in basic materials sector companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative approach using panel data regression analysis on 45 selected companies, resulting in 180 observations. The results show that, simultaneously, corporate governance variables do not have a significant effect on tax avoidance. Partially, independent commissioners and political connections do not significantly affect tax avoidance using either ETR or BTD, while institutional ownership only shows a significant effect when measured using BTD. These findings indicate that corporate governance mechanisms have not yet become the main determinants of corporate tax policies, which are more likely influenced by financial characteristics and operational strategies. The implications of this study highlight the importance of using multiple proxies in measuring tax avoidance and strengthening the implementation of corporate governance to ensure more transparent and accountable tax policies.